Improving Simple Writing Skills Through Picture and Picture Type Cooperative Learning Models in Class III Students of SD Negeri Tayem 01 Karangpucung - Ambar Ristianing Ayu; Amalia Nurul Azizah; Lili Riskiningtyas (Universitas Sebelas Maret, 2020)
This study aims to determine the improvement of simple essay writing skills through the picture and picture cooperative learning model in class III students of SD Negeri Tayem 01 Karangpucung. This type of research is Classroom Action Research. The research design used is the Kemmis and Mc model. Taggart. The data collection instruments used were student worksheets, observation sheets, interview question sheets, field notes, documentation, questionnaires, and questionnaire-filling guidelines. Based on the results of data analysis in the first cycle of the first meeting, the student's skills in writing simple essays showed 56% mastery learning with an average score of 67.5 and the second meeting showed 68% learning mastery with an average score of 71.25. After making improvements in cycle I, students' skills in writing simple essays increased. Based on the results of data analysis in cycle II, meeting I, the student's skills in writing simple essays showed 80% mastery with an average score of 76.25, and meeting II showed 88% mastery with an average score of 79.5. Based on the results of the study, it was shown that the picture and picture cooperative learning model could improve the skills of writing simple essays in class III students at SD Negeri Tayem 01 Karangpucung.